1990
DOI: 10.1029/jb095ib07p10973
|View full text |Cite
|
Sign up to set email alerts
|

Gravity estimation from STAGE, a Satellite‐to‐Satellite Tracking Mission

Abstract: An analysis was performed to determine the accuracy of estimating gravity anomalies using satellite-to-satellite tracking between the Space Transportation System (NASA's space shuttle) and the constellation of GPS satellites (STAGE: Shuttle-GPS Tracking for Anomalous Gravitation Estimation). Second time derivatives of the observed ranges, obtained from carrier phase measurements, between the low and high satellites provide in situ line-of-sight components of gravitation, as long as on-board accelerometers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Upadhyay et al [1989b] expanded this feasibility study with analyses of on‐orbit calibration of accelerometers and the on‐orbit transfer of alignment between experiment IMU (inertial measurement unit) and Shuttle IMU. Jekeli and Upadhyay [1990] performed a thorough analysis to predict the accuracy obtainable from such a satellite‐to‐satellite tracking mission. It was estimated that 2°x2° mean gravity anomalies can be recovered to an accuracy of 5 mgal.…”
Section: Space Gravity Missionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upadhyay et al [1989b] expanded this feasibility study with analyses of on‐orbit calibration of accelerometers and the on‐orbit transfer of alignment between experiment IMU (inertial measurement unit) and Shuttle IMU. Jekeli and Upadhyay [1990] performed a thorough analysis to predict the accuracy obtainable from such a satellite‐to‐satellite tracking mission. It was estimated that 2°x2° mean gravity anomalies can be recovered to an accuracy of 5 mgal.…”
Section: Space Gravity Missionsmentioning
confidence: 99%
“… Parker and Zumberge [1989] used ideal‐body analyses to show that results from the various geophysical experiments could be explained by unmodeled crustal densities; results of the tower experiment were thought to be due to unmodeled densities within 2 km of tower. However, a reanalysis of the experiment by Jekeli et al [1990] showed that the discrepancy was attributable to neglected topography mostly beyond 2 km from the tower and concluded that gravity behaves according to Newtonian law to an accuracy of several tens of microgals. Other tower experiments followed.…”
Section: Tests Of Newton's Lawmentioning
confidence: 99%
“…Moreover, this combination permits (at least in a post‐mission analysis) the separation of the full gravity vector from inertial and rotational accelerations, making a practical proposition of vector gravimetry: the simultaneous determination of gravity anomalies and deflections of the vertical, which in turn can be used to calculate geoid profiles by simple integration along the line traversed by a vehicle thus instrumented [Colombo, 1990c]. In space applications, Jekeli [1988], Upadhyay et al [1989], and Jekeli and Upadhyay [1990] describe the proposed STAGE experiment, where a GPS receiver would be installed in the Space Shuttle to map gravity from low altitudes, and in which an inertial navigation unit would be needed to separate gravitation from the forces of aerodynamic drag and solar radiation pressure.…”
Section: Gps Positioningmentioning
confidence: 99%
“…Although the orbit energy-based approach was first proposed by Wolff (1969) for direct measurement of the Earth's gravity field and has since been substantially investigated (see, e.g., Douglas et al 1980;Ilk 1983Ilk , 1986Jekeli and Upadhyay 1990;Rowlands et al 2002), Jekeli (1999) demonstrated that the naive version of Wolff's SST scheme is too simplified and can hardly be applicable to process real SST data. Jekeli (1999) then proposed a fully functional version of SST to recover the Earth's gravity field.…”
Section: Introductionmentioning
confidence: 99%